Yeasts Associated with Various Amazonian Native Fruits - Vegas C. (2020)
Yeasts, commonly present on the surface of fruits, are of industrial interest for the production of enzymes, flavorings, and bioactive compounds, and have many other scientific uses. The Amazonian rainforest may be a good source of new species or strains of yeasts, but their presence on Amazonian fruits is unknown. The aim of this study was to identify and characterize yeasts isolated from Amazonian native fruits using molecular and phenotypic methods. In total, 81 yeast isolates were obtained from 10 fruits species. Rep-PCR showed 29 strain profiles. Using a combination of restriction-fragment length polymorphism (RFLP) of the 5.8S-ITS region and D1/D2 sequencing of the 26S rRNA gene, 16 species were identified belonging to genera Candida, Debaryomyces, Hanseniaspora, Kodamaea, Martiniozyma, and Meyerozyma. The most dominant species were Candida tropicalis, Debaryomyces hansenii, Hanseniaspora opuntiae, and Hanseniaspora thailandica. H. opuntiae and H. thailandica showed the highest number of the strain profiles. Phenotypic profiles were variable between species, and even among strains. Screening for hydrolases showed lipolytic activity in only one isolate, while proteolytic, cellulolytic and amylolytic capabilities were not detected. Yeast presence among fruits varied, with cidra (Citrus medica) and ungurahui (Oenocarpus bataua) having the highest number of species associated. This investigation broadens the understanding and possible biotechnological uses of yeast strains obtained from Amazonian native fruits. © 2020 Carlos Vegas et al.